2009
DOI: 10.1183/09031936.00153108
|View full text |Cite
|
Sign up to set email alerts
|

Is treatment with ICS and LABA cost-effective for COPD? Multinational economic analysis of the TORCH study

Abstract: The TOwards a Revolution in COPD Health (TORCH) study was a 3-yr multicentre trial of 6,112 patients randomised to salmeterol (Salm), fluticasone propionate (FP), a Salm/FP combination (SFC) or placebo (P). Here the cost-effectiveness of treatments evaluated in the TORCH study is assessed.For four regions, 3-yr all-cause hospitalisation, medication and outpatient care costs were calculated. The sample was restricted to the 21 countries (n54,237) in which European quality of life five-dimension (EQ-5D) data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 28 publications
3
59
1
1
Order By: Relevance
“…57 This is well above the threshold used by the UK National Institute for Clinical Effectiveness (NICE) to assess cost effectiveness (£20-30,000 per QALY 58 ). A secondary economic analysis of the TORCH trial 59 estimated that salmeterol/fluticasone had an overall cost per QALY of $43,600 compared to placebo, SFC had a lower cost effectiveness ratio than either salmeterol or fluticasone alone ($197,000 and $78,000 per QALY respectively), and in this case the economic analysis supports the clinical evidence that combination therapy is the better treatment.…”
Section: Economic Issuessupporting
confidence: 49%
See 1 more Smart Citation
“…57 This is well above the threshold used by the UK National Institute for Clinical Effectiveness (NICE) to assess cost effectiveness (£20-30,000 per QALY 58 ). A secondary economic analysis of the TORCH trial 59 estimated that salmeterol/fluticasone had an overall cost per QALY of $43,600 compared to placebo, SFC had a lower cost effectiveness ratio than either salmeterol or fluticasone alone ($197,000 and $78,000 per QALY respectively), and in this case the economic analysis supports the clinical evidence that combination therapy is the better treatment.…”
Section: Economic Issuessupporting
confidence: 49%
“…Although a model may suggest that a drug is cost effective in a certain health economy it cannot automatically be assumed that it will be cost effective in all health economies. 60 In the secondary economic analysis of the TORCH trial, 59 there were geographical variations in the cost effectiveness of salmeterol/fluticasone, with an estimate of cost per QALY of $24,200 in Western Europe and $77,100 in the USA.…”
Section: Economic Issuesmentioning
confidence: 99%
“…Cost effectiveness evaluations for medications in COPD are much more complicated due to the small incremental improvements in outcomes compared with those seen in asthma, so that cost effectiveness is determined by willingness to pay (44,47). Single-entity ICSs are the least cost effective compared with LABAs or ICS/LABA combination, which is mostly attributable to the LABA component (47,48).…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…In the UK, it is commonly considered that treatments falling below £20,000 per QALY are likely to be considered cost-effective. At a threshold willingness to pay for a QALY of $50,000 (conventional value in the USA), the likelihood for the combination treatment, salmeterol and fluticasone being cost-effective is ,0.93, 0.01 and 0.03, respectively, in the Western European region, suggesting that the combination should be preferred to monotherapies on the grounds of cost-effectiveness [52]. In the OPTIMAL trial, the association of the salmeterol/fluticasone combination with tiotropium improved some health outcomes, including the number of exacerbations requiring hospitalisations versus tiotropium alone, but the incremental cost-effectiveness ratio per QALY (from $145,000 to $243,000) compared with tiotropium alone suggested that monotherapy with tiotropium is the most cost-effective choice [53].…”
Section: Economic Aspects Of Copd Pharmacological Treatmentsmentioning
confidence: 99%